The Infant Injury Database: A Tool for the Study of Injury Patterns in Medicolegal Investigations of Child Abuse. Issue 6 (2nd July 2019) - Soto Martinez, Miriam E.; Love, Jennifer C.; Pinto, Deborrah C.; Wiersema, Jason M.; Derrick, Sharon M.; Bachim, Angela; Greeley, Christopher; Donaruma‐Kwoh, Marcella; Truong, Van Thi Thanh; Gao, Si; Crowder, Christian M.
Abstract: In 2012, the Harris County Institute of Forensic Sciences began prospectively collecting injury data from pediatric autopsies. These data and associated case information from 635 pediatric cases are archived in the Infant Injury Database (IID). This paper introduces the IID to the forensic community and demonstrates its potential utility for child abuse and infant fatality investigations. The database is intended to be a source of evidence‐based research for coroners/medical examiners and clinicians in the recognition and diagnosis of child abuse. RR estimates were employed to quantify the relationship between individual autopsy findings to trauma‐related and nontrauma‐related causes of death. For example, unsurprisingly, the RR of trauma cases with multiple injury types is significantly greater than other causes of death, but the RR results provide a quantitative representation of the relationship. ROC curve modeling of the presence/absence of various injury types performed well at discriminating trauma from other causes of death (AUC = 0.96).